2006
DOI: 10.1177/10883576060210020601
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Static Picture Prompting and Video Prompting Simulation Strategies Using Group Instructional Procedures

Abstract: Two groups of three students with moderate mental retardation were instructed using group procedures to compare static picture and video prompting simulation strategies. An alternating treatments design was used to compare individual student task acquisition and maintenance performances of purchasing and banking skills. The results indicated that these two strategies were equally effective and efficient. Individual differences suggest that simulation strategy materials benefit student learning by displaying re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 28 publications
(48 reference statements)
3
108
0
Order By: Relevance
“…Undoubtedly, participants had different experiences, past reinforcement history and preferences. Therefore, they had various responses across the instructional methods, the selected tasks and the stimulus materials, which affected their performance [23,26]. For example, four participants (i.e., Gary, Alice, Stuart and Peter) achieved a better performance when VM was used, one (i.e., William) performed better during the SP condition, one (i.e., Roddy) in both in vivo modeling and SP conditions and two (i.e., George and Ted) performed equally well in all conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Undoubtedly, participants had different experiences, past reinforcement history and preferences. Therefore, they had various responses across the instructional methods, the selected tasks and the stimulus materials, which affected their performance [23,26]. For example, four participants (i.e., Gary, Alice, Stuart and Peter) achieved a better performance when VM was used, one (i.e., William) performed better during the SP condition, one (i.e., Roddy) in both in vivo modeling and SP conditions and two (i.e., George and Ted) performed equally well in all conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They found that VM was more effective as it led to faster acquisitions of the targeted behaviors and promoted the generalization of behavior changes. Alberto et al [25] and Cihak et al [26] compared the effectiveness and efficiency of SP versus VM on the acquisition and maintenance of community skills to students with moderate mental retardation. Both studies indicated that the strategies were effective in teaching the targeted skills and no functional differences between them were identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the many skills that have been taught effectively through simulations include locating items in a grocery store (Mechling & Gast, 2003), using a cell phone (Tabor et al, 2002), purchasing (Xin et al, 2005), banking skills (Davies et al, 2003;Cihak et al, 2006), and laundry skills (Taylor et al, 2002).…”
Section: Type Of Instructionmentioning
confidence: 99%